The Synergy of the Independent Learning Campus Programme at the Office of Population Control, Family Planning, Women's Empowerment, and Child Protection - Masrukin, Masrukin; Wardiyono, F.X; Sabiq, Ahmad; Wuryaningsih, Tri; Puspitasari, Elis; Rostikawati, Rin; Sulaiman, Adhi Iman (Technium Education and Humanities, 2024)
The COVID-19 pandemic has de facto transitioned into a post-pandemic phase, although it has not yet been officially declared endemic by the World Health Organization (WHO). This phenomenon necessitates the adoption of new adaptive strategies to enhance community empowerment. At this juncture, conducting research on Social Network Analysis (SNA) is crucial to developing a community empowerment model through the Independent Learning Campus Program under the Department of Population Control, Family Planning, Women’s Empowerment, and Child Protection (DPPKBP3A) in Banyumas Regency during the post-pandemic era. This research aims to identify, test, and implement a novel model of community empowerment through the independent learning campus program programme, particularly focusing on student internship initiatives in the post-pandemic context. The model will be implemented through a synergy between higher education institutions, local governments, and communities to address the impacts of the COVID-19 pandemic. The research will focus on developing a social network model in the post-pandemic era and will be conducted in three stages.The first stage involves exploring and confirming the SNA of the independent learning campus programme during the COVID-19 pandemic in rural and urban areas using SNA analysis methods. The second stage focuses on applying the independent learning campus program empowerment model in rural and urban areas during the pandemic. The third stage involves disseminating and implementing the independent learning campus program empowerment model policy in rural and urban areas at the regency level in Banyumas. Preliminary findings highlight a significant public interest in the issue of stunting in Indonesia, as evidenced by Google Trends analysis. From 20 March 2022 to 19 March 2023, there was a 50% to 55% increase in web searches using the keyword “stunting” in Indonesia. This indicates a growing public interest in the stunting issue over the past year.